THE EFFECT OF AGE, QUALITY AND GENDER ON CUSTOMERS' INTEREST IN DRINKING COFFEE AT COFFEE SHOP JABU HELA, MEDAN CITY - Arjun Setiawan Ndraha; Farhan Zacky; Deni Faisal Mirza (RADJA PUBLIKA, 2024)
This study aims to investigate the influence of age, coffee quality, and gender on customer interest in consuming coffee at the Jabu Hela Coffee Shop in Medan City. The method used is quantitative through multiple linear regression analysis. The research findings indicate that the age variable has a positive but partially insignificant effect on customer interest. Meanwhile, coffee quality and gender have a partially significant positive effect on customer interest. Simultaneously, the variables of age, coffee quality, and gender have a positive and significant effect on customer interest. These findings emphasize the importance of maintaining product quality and understanding demographic preferences to increase consumer interest.